Early Eocene orthophragminids and alveolinids from the Jafnayn Formation, N Oman: significance of Nemkovella stockari Less & Özcan, 2007 in Tethys. Issue 3 (2nd July 2016) - Özcan, Ercan; Abbasi, İftikhar Ahmed; Drobne, Katica; Govindan, Abiraman; Jovane, Luigi; Boukhalfa, Kamel
Abstract : The upper member of the Jafnayn Formation in Wadi Rusayl and Al Khoud, Seeb Area in north Oman contains Nemkovella stockari Less & Özcan, 2007, an Early Eocene orthophragminid recorded here for the first time from the Arabian Peninsula. N. stockari, the only orthophragminid identified in Jafnayn Formation, is quite distinct from any other species from Tethys in having spiral and orbitoidiform chambers around the isolepidine embryon developed before the onset of annular chambers. The Oman specimens exhibit equal-sized principal auxiliary chambers and symmetrical spirals and are assigned to N. stockari bejaensis Özcan, Boukhalfa & Scheibner, 2014, an advanced form of the N. stockari lineage. The associated alveolinids, revised in this study, rotaliids and other age-diagnostic foraminiferal taxa in the transgressive basal part of the upper member have enabled us to revise the age as middle Ilerdian (Early Eocene), assignable to SBZ 7/8 and 8; OZ 3/4. Integrating a new record of this species from Arabian Plate margin in Belen, S Turkey, and previous records from north Africa, N. stockari appears to be a diagnostic marker for the Early Eocene along the southern peri-Tethys platforms, facilitating the Tethyan correlation by orthophragminids. The palaeobiogeographic distribution of N. stockari is discussed.